Pengaruh Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada Pt Map Mitra Adiperkasa Active Cabang Kidz Station Pondok Indah Mall Jakarta Selatan - Dede Kurnia Putra; Shella Puspita Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this research is to determine whether there is an influence of work discipline and motivation on employee performance, either partially or simultaneously, at PT Mitra Adiperkasa Active, Kidz Station Branch, Pondok Indah Mall, South Jakarta. This quantitative study involves employees at PT Mitra Adiperkasa Active, Kidz Station Branch, Pondok Indah Mall, South Jakarta, using a saturated sampling technique distributed to 57 respondents. Data was collected using questionnaires and analyzed with descriptive statistics, classical assumption tests, statistical tests, and hypothesis testing with SPSS 26 software. The findings indicate a significant influence of work discipline and motivation on employee performance. The t-test value for the work discipline variable is 4.326, which is greater than the t-table value of 2.004, with a significance value of 0.0 < 0.05, indicating a significant influence of work discipline on performance. Similarly, the t-test value for the motivation variable is 5.576, which is greater than the t-table value of 2.004, with a significance value of 0.0 < 0.05, indicating a significant influence of motivation on performance. The simultaneous influence of work discipline and motivation on employee performance is confirmed by the regression equation Y = 1.502 + 0.444(X1) + 0.530(X2), with a correlation coefficient (R) of 0.849, indicating a strong relationship. The determination coefficient value shows F-calculated > F-table (152.042 > 2.780), further supported by a significance value of < 0.05 (0.000 < 0.05).